2019
DOI: 10.1155/2019/9187978
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants as Adjuvants in Periodontitis Treatment: A Systematic Review and Meta-Analysis

Abstract: This systematic review with meta-analysis aimed to evaluate the effect of antioxidants as an adjuvant in periodontitis treatment. The following databases were consulted: PubMed, Scopus, Web of Science, Cochrane, Lilacs, OpenGrey, and Google Scholar. Based on the PICO strategy, the inclusion criteria comprised interventional studies including periodontitis patients (participants) treated with conventional therapy and antioxidants (intervention) compared to patients treated only with conventional therapy (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 57 publications
1
33
0
1
Order By: Relevance
“…Seventeen articles met the criteria and were included for qualitative analysis. Thirteen studies reported subgingival application of CHX gel adjunct to SRP at selected sites with a moderate to deep probing depth (at least 4 mm in all studies) [8][9][10][25][26][27][28][29][30][31][32][33][34]. Nine studies were split-mouth RCTs [10,12,[27][28][29][32][33][34][35], four were parallel RCTs [11,26,30,31] and three studies used a placebo in the control [12,31,33].…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen articles met the criteria and were included for qualitative analysis. Thirteen studies reported subgingival application of CHX gel adjunct to SRP at selected sites with a moderate to deep probing depth (at least 4 mm in all studies) [8][9][10][25][26][27][28][29][30][31][32][33][34]. Nine studies were split-mouth RCTs [10,12,[27][28][29][32][33][34][35], four were parallel RCTs [11,26,30,31] and three studies used a placebo in the control [12,31,33].…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…In regards to this issue, adjunctive systemic and localized antibiotics have been applied to compensate for the limitation of mechanical therapy. Despite the rapid development of a variety of adjunctive local periodontal treatments in recent years, such as metformin, antioxidants, photodynamic treatment and so on [7][8][9], chlorhexidine (CHX) remains one of the most effective local antimicrobial agents, and is widely used for the local treatment of periodontitis [10][11][12][13]. Through the rapid attraction of the negatively charged bacterial cell surface to the cationic CHX molecule, CHX shows strong antibacterial activity in the periodontal pocket, along with a lack of toxicity, incompliance from patients and an emergence of resistance microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…9 SOD is a primary enzyme which scavenges oxygen free radical, hence it is an important antioxidant enzyme that protects tissues against oxidative injury resulting from oxidative stress. 10 Antioxidant therapy for treatment of periodontitis has given positive results as stated in a systemic review by Castro et al 11 CoQ10, which is also known as ubiquinone, because of its ubiquitous presence, is an antioxidant enzyme and has been studied widely for its effect in treatment of periodontal disease. [12][13][14][15][16][17][18][19][20] In the present study, an attempt had been made to evaluate the efficacy of CoQ10 in reduction of clinical parameters (GI, PI, PPD, and CAL) and its effect on SOD in GCF as an adjunct to Phase 1 periodontal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen articles met the criteria and were included for qualitative analysis. Thirteen studies reported subgingival application of CHX gel adjunct to SRP at selected sites with a moderate to deep probing depth (at least 4mm in all studies) [8][9][10][25][26][27][28][29][30][31][32][33][34] . Nine studies were split-mouth RCTs 10,12,[27][28][29][32][33][34][35] , four were parallel RCTs 11,26,30,31 and three studies used a placebo in the control 12,31,33 .…”
Section: Description Of the Included Studiesmentioning
confidence: 99%